THE IMPACT OF CREATIVITY AND INNOVATION ON THE LEVEL OF KNOWLEDGE AND UNDERSTANDING OF TOTAL QUALITY MANAGEMENT BENEFITS AMONG HEALTHCARE MANAGERS IN JORDAN - Salaheldin, Salaheldin Ismail; Fathi, Samia; Shawaheen, Mohammad S. (European Scientific Journal, ESJ, 2015)
This study aims to investigate the effect of creativity and innovation on the level of knowledge and understanding of total quality management TQM benefits in healthcare sector. A survey conducted through selfadministered questionnaires distributed among healthcare managers working in six Jordanian hospitals. The questionnaire consisted of three parts; demographic variables, creativity and innovation data, and TQM level of knowledge and understanding data. Study sample included 292 respondents. The results found that there is a statistically significant impact for the patterns of creativity and innovation on the overall level of knowledge and understanding of TQM benefits in the Jordanian healthcare sector